The Influence of Access to Financing and Financial Management on the Performance of MSMEs in Makassar City - Aprilia Maya; Andryanus Paridy; Johannes Baptista Halik (Journal of Marketing Management and Innovative Business Review, 2025)
This study aims to analyze the influence of access to financing and financial management on the performance of MSMEs in Makassar City. The research involved 96 business actors as samples, determined using the Lemeshow formula. A quantitative approach was employed, utilizing both primary and secondary data. Primary data were collected through the distribution of questionnaires to micro business actors in the culinary sector. Hypothesis testing was conducted using the Smart PLS software. The results of the analysis indicate that: 1) Access to financing has a significant effect on MSME performance; 2) Financial management has a significant effect on MSME performance; and 3) Both variables simultaneously exert a positive and significant influence on MSME performance. .